Scientific Research of Driving Training and Testing in Vietnam: Current Status and Challenges - Nguyen, Xuân Trung (Journal of Technical Education Science, 2022)
It can be said that scientific research is always an important basis for improving the quality of driving training and testing. However, this activity is both lacking and weak in our country: Searching on domestic and international scientific databases only collected 39 articles in domestic journals, published from 2012 to 2021. In which, it can be temporarily divided into 13 research problems, but in general, it is quite narrow in scope and discrete. Only 7/370 driving school participated in these studies, which were colleges, universities and 1 academy, the rest were 2 other universities and 1 individual. There is no scientific journal with a separate category for driving training and testing. This is obviously a big challenge for traffic safety, vocational education development and world scientific integration. Investments and initial research orders from The Government can be to help overcome.